Identification of shared neoantigens derived from frameshift mutations in the APC gene - Zhao, Peng; Effenberger, Clara; Matsumoto, Saki; Tanaka, Toshihiro; Nakamura, Yusuke; Kiyotani, Kazuma (Frontiers in Immunology, 2025)
Recent advances of cancer immunotherapy have identified neoantigens as essential targets for personalized treatments. However, since neoantigens are generally unique in individual cancers, neoantigen therapies that are more broadly applicable are eagerly awaited. Shared neoantigens, derived from recurrent mutations found across multiple patients, are considered to be a challenging, but promising approach. Here we analyzed shared frameshift neoantigens derived from frameshift indels in TCGA exome sequencing data and identified 760 possible recurrent frameshift mutation clusters (FSCs) that share frameshifted open reding frames and premature stop codons. Among them, we investigated FSCs in the APC gene (APC-F2-1472* and APC-F3-1512*) and identified HLA-A*24:02-restricted frameshift neoantigen peptides that elicited specific CD8+ T cell responses. Subsequently we identified their corresponding T cell receptor (TCR) sequences and generated genetically-engineered T cells expressing these APC frameshift neoantigen-specific TCRs. These engineered T cells specifically recognized target cells presenting these neoantigens and cytotoxic activity against them, supporting the therapeutic potential of targeting APC frameshift neoantigens in cancer immunotherapy. This study provides compelling evidence for the development of neoantigen-based therapies targeting common frameshift peptides, offering a promising approach for more effective, relatively broadly applicable immunotherapeutic strategies that could benefit a subset population of cancer patients.